A contract law approach to private censorship of art on social media platforms - Gabriel Ernesto Melian Pérez; Nausikaä El-Mecky (IDP)
The censorship of artists on social media impacts their freedom of expression and their ability to monetize and engage with their audiences. Furthermore, this fosters a process of cultural standardization. Several legal arguments have been raised against art censorship in social media platforms, mainly based on public law, however, they are not effective in all jurisdictions, as demonstrated by U.S. case law. The purpose of this paper is to shift the spotlight and provide solutions from a private law perspective, specifically from contract law. The main argument here is that courts should abandon their traditional bilateral/vertical approach and embrace a more nuanced one that better reflects the complexity of the relationships taking place in social media. This would give those affected access to concrete contractual remedies and allow for greater control over the content moderation process.